President’s Message: Harassment in the Workplace - Hill, Marlene (Operating Room Nurses Association of Canada Journal, 2001)
The very important basic principle of “Refuse to accept or condone any form of harassment” was intentionally omitted from a previous President’s message titled “Basic Principles” (June, 2000 CORNJ) as I thought it deserved to be given special and separate consideration. For proper timing, it was necessary to present the messages on “Certification” and “Standards” first.